Effects of Oral Hypoglycemic Drugs on Flow Rate and Protein Composition of Saliva in Patients with Diabetes Mellitus - Fayhaa AM Al- Mashhadane (University of Mosul, College of Dentistry, 2011)
Aims: To study the effects of both diabetes mellitus and oral hypoglycemic drugs (metfomin) on salivary flow rate and total protein levels of saliva and to compare them with control healthy subjects and to determine their effects on oral health of these patients. Materials and Methods: This study was carried out on 45 individuals (27 males and 18 females); 15 individuals of them were healthy subjects and considered as control group. The second group which comprised 15 patients with diabetes mellitus and received no any treatment (uncontrolled).The third group, diabetic patients were treated with metformin only. Subjects were selected from the out patients attending Oral Surgery Department, College of Dentistry-University of Mosul. The samples of saliva were collected and salivary flow rates and total protein was determined for each individual, then its relation to oral health was measured according to Simplified Oral Hygiene Index by Greene and Vermillion. Results: One way analysis of variance was performed and showed that their were significant differences among all study groups for both salivary flow rate and total salivary protein concentration .The results of Duncan's Multiple analysis range test showed that there were no significant differences in salivary flow rates and total salivary protein concentrations between first and third groups while significant differences were seen between first and second and between second and third groups .For oral health scores , there was no significant differences between first and third groups while significant differences were observed between first and second and between second and third groups. Conclusions: Changes in salivary flow rates and salivary protein concentrations can result from diabetes mellitus which can affect oral health of these patients, while oral hypoglycemic drugs had no such effects